Sintering of Multilayered Porous Structures: Part II–Experiments and Model Applications. Issue 8 (18th May 2013) - Ni, De Wei; Olevsky, Eugene; Esposito, Vincenzo; Molla, Tesfaye T.; Foghmoes, Søren P. V.; Bjørk, Rasmus; Frandsen, Henrik L.; Aleksandrova, Elena; Pryds, Nini; Bordia, R.
<x xml:space="preserve">Abstract</x> Experimental analyses of shrinkage and distortion kinetics during sintering of bilayered porous and dense gadolinium‐doped ceria Ce0.9Gd0.1O1.95−δ structures are carried out, and compared with the theoretical models developed in Part I of this work. A novel approach is developed for the determination of the shear viscosities ratio of the layer fully dense materials. This original technique enables the derivation of all the input parameters for the bilayer sintering modeling from one set of optical dilatometry measurements, including the conversion between real and specific times of sintering, the layers' relative sintering intensity, and the shear viscosities ratio of the layer fully dense materials. These optical dilatometry measurements are conducted simultaneously for each individual layer and for a symmetric trilayered porous structure based on the two layers utilized in the bilayered system. The obtained modeling predictions indicate satisfactory agreement with the results of sintering of a bilayered cerium–gadolinium oxide system in terms of distortion and shrinkage kinetics.